Density impact on toroidal rotation in Tore Supra: experimental observations and theoretical investigation. (4th February 2015) - Bernardo, J; Fenzi, C; Bourdelle, C; Camenen, Y; Arnichand, H; Bizarro, João P S; Cortes, S; Garbet, X; Guimarães-Filho, Z O; Aniel, T; Artaud, J-F; Clairet, F; et al.
Abstract: The effect of plasma density on toroidal rotation was examined in density ramp-up experiments at a plasma current of 1 MA and a toroidal magnetic field of 3.6 T in Tore Supra ohmic discharges. Experimental measurements have shown that the toroidal rotation amplitude is reduced at all radii when increasing the plasma density, although it remains in the counter-current direction. Neoclassical predictions including ripple-induced toroidal friction are in qualitative agreement with such observations. However, in the core ( r / a < 0.5) the plasma accelerates at n l ∼ 3 × 10 19 m −2 and breaks again above n l ∼ 3.5 × 10 19 m −2 . This rotation bifurcation did not appear to be correlated to a possible influence of the sawtooth activity. Nonetheless, quasi-linear gyrokinetic simulations have shown that the transition of the nature of linear microinstabilities from ITG-TEM to pure ITG occurs at n l ∼ 3 × 10 19 m −2, which could indicate a change on the turbulence driven contributions and explain the deviation from neoclassical predictions in the plasma core.